2015
DOI: 10.1111/epi.13030
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of direct medical costs in a large cohort of consecutively enrolled patients with refractory epilepsy in Italy

Abstract: SUMMARYObjective: To evaluate direct medical costs and their predictors in patients with refractory epilepsy enrolled into the SOPHIE study (Study of Outcomes of PHarmacoresistance In Epilepsy) in Italy. Methods: Adults and children with refractory epilepsy were enrolled consecutively at 11 tertiary referral centers and followed for 18 months. At entry, all subjects underwent a structured interview and a medical examination, and were asked to keep records of diagnostic examinations, laboratory tests, specialis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 28 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…Specifically, prior research for the overall adult epilepsy population has found that patients with unmanaged disease have significantly more healthcare provider visits than those with effectively controlled seizures [31]. Although the annual costs for AEDs were not collected in the current study, prior research suggests that one of the biggest components of overall direct costs is AED-related costs (children and adults, 8.2% IGE) [32].…”
Section: Discussionmentioning
confidence: 84%
“…Specifically, prior research for the overall adult epilepsy population has found that patients with unmanaged disease have significantly more healthcare provider visits than those with effectively controlled seizures [31]. Although the annual costs for AEDs were not collected in the current study, prior research suggests that one of the biggest components of overall direct costs is AED-related costs (children and adults, 8.2% IGE) [32].…”
Section: Discussionmentioning
confidence: 84%
“…In addition, the economic burden of patients with controlled epilepsy differs from that of patients with refractory epilepsy, but little is known about the specific burden for those treated with VNS or DBS. 27 , 42 , 43 Second, short‐term trial evidence was extrapolated to a lifetime time horizon. This entailed that patients were not able to transition between health states after the follow‐up time of the trial (except when patients died in the model).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, health pre‐surgical care costs of epilepsy increase with the number of comorbidities . The highest cost is for antiepileptic drugs (AEDs), which account for about 50% of the total cost according to recent Italian and Chinese studies . AEDs available in the last decades are somewhat effective but much more expensive.…”
mentioning
confidence: 99%